Impact of cryogenic treatment on the microstructure and properties of a thermo-mechanically processed Cu-11Fe composite. Issue 1 (1st September 2022) - Liu, Keming; Jin, Ying; Fu, Kai; Shi, Jinke; Li, Mulin; Wen, Jiahao; Zhang, Yanyan; Shen, Zhi; Huang, Zhikai
Abstract: The conductivity and strength of Cu-Fe composites are contradictory. Cryogenic treatment is a promising process to improve the conductivity and strength of materials at the same time. The impact of cryogenic treatment on a thermo-mechanically processed Cu-11Fe composite was studied using a digital micro-ohmmeter, a tensile testing machine and optical microscopy. The average size of the iron grain in the cryogenically treating Cu-11Fe alloy decreased and the distribution was more uniform after the cryogenic treatment. The grain refinement and the distribution uniformity increased with improving cryogenic treatment time. The elongation to fracture and tensile strength improved first with increasing cryogenic treatment time to a peak value at 18 h and 12 h respectively, and subsequently tended to be stable at longer cryogenic treatment time. The electrical resistivity decreased first with the increase of cryogenic treatment time, then reached an electrical resistivity valley value at 18 h, and subsequently tended to be stable at longer cryogenic treatment time.